Particle flux–gradient relationships in the high Arctic: emission and deposition patterns across three surface types - T. Mathes; H. Guy; H. Guy; J. Prytherch; J. Kojoj; I. Brooks; S. Murto; P. Zieger; B. Wehner; M. Tjernström; A. Held (Atmospheric Chemistry and Physics, 2025)
The Arctic is experiencing a warming much faster than the global average and aerosol–cloud–sea–ice interactions are considered to be one of the key features of the Arctic climate system. It is therefore crucial to identify particle sources and sinks to study their impact on cloud formation and cloud properties in the Arctic. Near-surface particle and sensible heat fluxes were measured using the gradient method during the ARTofMELT Arctic Ocean Expedition 2023. A gradient system was deployed to calculate sensible heat and particle fluxes over three different surface conditions: wide lead, narrow lead, and closed ice. To evaluate the gradient measurements, sensible heat fluxes and friction velocities were compared with eddy covariance data. The strongest mean sensible heat fluxes, ranging from 16 to 51 W m−2, were observed over wide lead surfaces, aligning with measurements from the icebreaker. In contrast, closed ice surfaces had weak, often negative, sensible heat fluxes. Wide leads acted as a particle source, with median net particle emission fluxes of 0.09 × 106 m−2 s−1. Narrow lead surfaces exhibited both net emission and net deposition, though the particle fluxes were weaker. Closed ice surfaces acted as a particle sink, with normalized fluxes around 0.06 cm s−1. The gradient method was found to be effective for measuring both sensible heat and particle fluxes, allowing flexible deployment over different surface types. This study addresses the critical need for improved quantification of turbulent vertical particle fluxes and related processes that influence the local particle number budget in the high Arctic.